Environmentally Sustainable Livestock Production - Ilkka Leinonen (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book looks at key research covering a wide range of aspects of environmental sustainability and the mitigation of environmental impacts of livestock production, including emissions of greenhouse gases (carbon dioxide, methane, nitrous oxide), nitrogen and phosphorus excretion, ammonia emissions, land use and land management, and use of energy and other resources. All the globally most important livestock species (beef and dairy cattle, pigs, broiler chicken and laying hens) are covered in the book. The mitigation methods assessed in the papers include general system changes, changes in feeding, improvement of animal health, and new technologies of manure management. The scope of the papers included in this book ranges from farm level mitigation methods to national level system changes. This book also addresses methodological development in assessing the environmental sustainability of the livestock production chains, including holistic methods, such as environmental and social life cycle assessment (LCA) and other modeling approaches.